Sex Differences in the Effect of Inflammation on Subjective Social Status: A Randomized Controlled Trial of Endotoxin in Healthy Young Adults - Moieni, Mona; Muscatell, Keely A.; Jevtic, Ivana; Breen, Elizabeth C.; Irwin, Michael R.; Eisenberger, Naomi I. (Frontiers in Psychology, 2019)
It has been established that inflammation leads to a variety of changes in social experience, but one area of social experience that has been overlooked is subjective social status. Furthermore, given sex differences in the relationship between inflammation and social status, males may be more sensitive to inflammation-induced changes in social status. However, no previous studies in humans have examined this possibility. In the present study, healthy young participants (n = 115) were randomly assigned to receive either endotoxin, an experimental inflammatory challenge, or placebo. Participants reported their subjective social status at baseline (prior to injection), and approximately two hours later (time of peak inflammatory response for the endotoxin group). Results, using ANCOVA analyses, indicated that males exposed to endotoxin, but not females, reported lower levels of subjective social status at the peak of inflammatory response (vs. placebo). These results suggest that males may be more sensitive to the effects of inflammation in certain social domains, such as perceived social status.